Analysis of Learning Desk Design for Children Mental Retardation at Extra Ordinary School of Putra Mandiri, Cilacap - Supriatin (Indonesian Journal of Disability Studies, 2018)
The design of study desks in special schools is generally made equal to the purpose for the convenience of students in learning so as to help students in receiving the lessons well. The purpose of this study was to analyze and redesign the table in grade IV child tunagrahita. This research uses descriptive qualitative method through exploration approach. This study used observation and unstructured interviews with headmasters, classroom teachers, students of grade IV tunagrahita students at SLB Putra Mandiri Kawunganten in Cilacap. The result of this research is proposed in the form of analysis of table design for learners so as to produce more ergonomic desk.